EVALUATION OF DIFFERENT GLADIOLUS CULTIVARS FOR GROWTH, FLOWERING, SPIKE YIELD AND CORM YIELD UNDER SAURASHTRA REGION OF GUJARAT - ANKIT CHOURASIA; R. R. VIRADIA; H. ANSAR; SHUBHAM N MADLE (The Bioscan, 2014)
The aim of the study was to find out the suitability of ten gladiolus varieties for cultivation under Saurashtra region of Gujarat in terms of growth, flowering, spike yield and corm yield characters during 2011-2012. The experi- ment was arranged in Randomized Block Design with three replications. There were significant difference among the varieties with respect to vegetative, floral and yield characters. Maximum plant height (122.87 cm) was recorded in ‘Poppy Tear’. ‘American Beauty’ produced maximum number of leaves per plant (11.57). Red Majesty was recorded maximum leaf length (69.33 cm). ‘White Prosperity’ recorded maximum days to sprouting of corm (26.73), leaf width (4.60 cm), spike length (99.80 cm) and rachis length (67.80 cm). ‘Red Beauty’ required maximum, number of days to first spike emergence (114.40), diameter of daughter corm (3.37 cm), weight of daughter corm (61.01 g) and largest size index of daughter corm (11.51 cm2). ‘Candiman’ was recorded the maximum spike diameter (1.230 cm), floret neck diameter (1.97 cm), diameter of floret (15.50 cm), longest duration of flowering (24.00), number of florets per spike (23.73), number of spikes per plant (1.87), number of corms per plant (1.80), number of cormels produced per plant (98.00) and weight of the cormels (96.61). It was concluded that variety ‘Candiman’ was found best for cultivation under Saurashtra region of Gujarat in terms of growth, flowering, spike yield and corm yield characters.